IDENTIFY FACTORS AFFECTING STUDENT ACHIEVEMENT USING THE BINARY LOGISTIC REGRESSION ANALYSIS: IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI SISWA MENGGUNAKAN ANALISIS REGRESI LOGISTIK BINER - Nursalam,; Hamzah, Qardawi; Baharuddin,; Kusumayanti, Andi; A. Sriyanti, (MaPan : Jurnal Matematika dan Pembelajaran, 2023)
The success of students in completing their study program is indicated by the achievements reflected in their Grade Point Average (GPA). Grade Point Average (GPA) is expressed in numerical form and is an academic achievement calculated based on all courses taken in all semesters that have been passed by students. This study aims to obtain a model of external factors that affect Grade Point Average (GPA) and variables that affect Grade Point Average (GPA). The response variable in this study is Grade Point Average (GPA) which is categorical and divided into two categories. The method used is binary logistic regression analysis. This study used primary data with the research subjects being second, third, and fourth-semester students in the Mathematics Education Department of Alauddin Makassar State Islamic University. The indicators on the instrument can be categorized as valid and reliable to measure service variables, learning, facilities and infrastructure, and student interest in entering college. The results of binary logistic regression analysis show that service has a significant effect on Grade Point Average (GPA), besides that learning, facilities, infrastructure, and the number of students enrolling in college have an effect but are not significant on Grade Point Average (GPA).